Konsep Aplikasi Masak Yuk! dengan Menggunakan Prinsip Design Thinking - Charity Latanza Indahsari; Iwan Sukoco (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2020)
Design thinking is a design method that can provide a solution-based approach to solving a problem and is very useful in overcoming very complex problems. One of the technological developments in the culinary field is the emergence of applications that contain a variety of recipes. The purpose of this research is to make it easier for people who want to cook food at home without having to search one by one the ingredients to be cooked but by buying various packages of ingredients that are sold and can enjoy the video tutorial features of each existing food package. The method used in this research is descriptive qualitative. Researchers used design thinking as an approach and also the thought process in finding concepts from an application. In addition, there are five stages in design thinking, namely empathy, define, ideate, prototype and test. The application "Masak Yuk!" is an application that contains cooking tutorials, tips about cooking and selling food ingredients packages. By using design thinking that was designed according to the needs of the community, the product could be well defined and the overall concept could be displayed.